Progression in youth soccer: Selection and identification in youth soccer players aged 13-15 years - Bidaurrazaga-Letona, I.; Lekue, J. A.; Amado, M.; Gil, S. M. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to identify the factors that are important for the identification and selection of young soccer players. Ninety-four adolescent soccer players from the under-13 (U13; age = 12.3 ± 0.3 years; n = 50) and under-15 (U15; age = 14.0 ± 0.2 years; n = 44) categories belonging to a professional club participated in the study. Anthropometric measurements, physical tests (sprint, agility, endurance and jump), and maturity status (age at peak height velocity) were recorded over 4 seasons. Comparisons were performed among new players joining the club (Enter players, n = 15), players progressing to the next age category (Club players, n = 54), and players leaving the club (Deselected players, n = 25). A 2-way repeated measures analysis of variance (ANOVA) was performed to determine if significant differences existed between groups and testing time. Better physical performance and improvements observed during the season in performance were found to be one of the main factors for U13 players to continue in the club (p < 0.05-0.001). In the U15 group, although body size, maturation and physical performance appeared to be the most important characteristics for being identified to play in the club (p < 0.05), Club players demonstrated better improvements during the season (p < 0.05). Overall, these results indicate that the identification or promotion of players by coaches depends on indicators which are age-dependent. Therefore, this study has shown that the talent identification program was more a selection process than a promotion process, selecting and identifying a posteriori rather than a priori.